Crystal structure of carbonyl{hydridotris[3-phenyl-5-methylpyrazol-1-yl]borato-κ3N,N′N′′}copper(I), C31H28BCuN6O - Fujisawa, Kiyoshi; Yabe, Makoto; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C31H28BCuN6O, monoclinic, P21/n (no. 14), a = 11.506(3) Å, b = 16.122(3) Å, c = 15.805(3) Å, β = 99.433(3)°, V = 2892.2(11) Å3, Z = 4, Rgt(F) = 0.0501, wRref(F2) = 0.1260, T = 193(2) K.